Nivolumab-induced immune mediated eczematous dermatitis in patient with carcinoma of buccal mucosa - Shetty, Madhurya; Venkategowda, Anuradha H.; Maka, Vinayak V. (International Journal of Basic & Clinical Pharmacology, 2023)
An elderly man undergoing treatment for carcinoma of left buccal mucosa experienced the appearance of skin lesions on his chest, both upper limbs, and both lower limbs after receiving the first cycle of nivolumab therapy. A biopsy report confirmed that the patient had eczematous dermatitis, which was believed to be induced by nivolumab. Patient received symptomatic treatment with Prednisolone, Clobetasol propionate and Fusidic acid. The Skin lesions improved, and subsequently Framycetin cream was recommended, resulting in no further recurrence of lesion. Clinicians should remain vigilant about development of T-cell activation-related skin disorders when administrating immune checkpoint inhibitors, such as nivolumab.